Network slicing deployment method based on isolation level - Qirun PAN; Kaizhi HUANG; Wei YOU (网络与信息安全学报)
In order to balance the performance isolation requirements and security isolation requirements of network slicing,a network slice deployment method based on isolation level was proposed.The method first determined the isolation level of the network slice instance from the aspects of performance isolation and security isolation.When deploying the virtual nodes in the appropriate location,not only ensured that all network slice instances could reach their respective performance levels and security levels,but also isolated them.The gradation difference started to limit the coexistence condition of the virtual node.Then the integer linear programming method was used to model the problem,and the deployment cost was minimized as the objective function.Finally,the particle swarm optimization algorithm based on genetic algorithm was used to find the final deployment result.The simulation results show that the method has lower deployment cost and higher benefit-to-cost ratio,and can guarantee both performance and security.